Arboreal Locomotion in Eurasian Harvest Mice Micromys Minutus (Rodentia: Muridae): The Gaits of Small Mammals. Issue 1 (23rd March 2017) - Karantanis, Nikolaos‐Evangelos; Rychlik, Leszek; Herrel, Anthony; Youlatos, Dionisios
GRAPHICAL ABSTRACT: Our findings in Micromys minutus suggest that gait metrics do not greatly differ between larger and smaller arboreal mammals, except for how velocity is regulated. Furthermore, they also show that diagonal sequence gaits are not necessary for terminal branch quadrupedalism at a small body size. ABSTRACT: Body size imposes significant constraints on arboreal locomotion. Despite the wealth of research in larger arboreal mammals, there is a lack of data on arboreal gaits of small mammals. In this context, the present study explores arboreal locomotion in one of the smallest rodents, the Eurasian harvest mice Micromys minutus (∼10 g). We examined gait metrics (i.e., diagonality, duty factor [DF], DF index, velocity, stride length, and stride frequency) of six adult male mice on simulated arboreal substrates of different sizes (2, 5, 10, and 25 mm) and inclinations (0 0 and 45 0 ). Micromys minutus employed slow, lateral sequence symmetrical gaits on the smaller substrates, which shifted to progressively faster symmetrical gaits of higher diagonality on larger substrates. Both ascents and descents were associated with a higher diagonality, and ascents with a higher DF index compared to horizontal locomotion, underscoring the role of the grasping hind feet. Velocity increase was brought about primarily by an increase in stride frequency, a pattern often encountered in other small mammals, with a secondary and significant contribution of stride length. These findings indicate that, except for velocity and the way it is regulated, there are no significant differences in gait metrics between larger and smaller arboreal mammals. Moreover, the locomotor adaptations of Eurasian harvest mice represent behavioral mechanisms that promote stable, safe, and continuous navigation along slender substrates and ultimately contribute to the successful exploitation of the arboreal milieu.